Narrativas audiovisuais nas redes sociais: o consumo como elemento de identidade na campanha da Panvel - Mantello, Paulo Francisco [UNESP] (2015)
In order to answer the demands of users of the new digital media, experimentations have been made in the media communication field. Adversitising has significantly contributed in this quest using audiovisual narratives and storytelling resource. This paper investigates the use of narrative in audiovisual products whose intent is to convey brand content. This research has as object two films of an advertising campaign from Panvel Pharmacies, hosted on Youtube and shared by the enterprise principally on Facebook: audiovisual The History of Lilinho (2011) and The History of Sofia (2012). The research analyzes how the narrative seeks to involve the consumer emotionally to establish a bond with the brand from the psychological emptiness of human being. It is understood that there is a search for identity that stories solidify momentarily in a kind of advertising denial. Social networking sites appear to enhance this search with the possibility of interaction and production of what is consumed. One way to explore the power of narrative has been the adaptation of atistic and literacy works to attract and engage consumers. The analysis was promoted by narrative study from the intersection of Communication and Psychology. Salmon and Nuñez were used to the case study to deal with storytelling; Kotler for marketing and advertising; Lévy and Recuero to new technologies and media; and Baudrillard and Bauman to society and consumption. In the fields of audiovisual and adaptation Aumont and Bulhões were adopted, also Jullier and Marie to assist in film analysis. It sought further knowledge in psychoanalysis, in Lacan